Randomized clinical trial of a motivational interdisciplinary intervention based on the transtheoretical model of change for lifestyle modification in overweight/obese adolescents: MERC study protocol - Ribeiro, Fernanda A.; Boff, Raquel M.; Feoli, Ana M. P.; Gustavo, Andreia S.; Donadio, Márcio Vinícius Fagundes; Oliveira, Margareth S. (International Journal of Clinical Trials, 2016)
Background: Obesity worldwide has more than doubled between 1980 and 2014, and this number has grown substantially in adolescents. An increase in this number can be prevented with the modification of lifestyle, healthy food choices and regular physical activity. The aim of this study is to evaluate the effect of a motivational interdisciplinary intervention based on the transtheoretical model of change for lifestyle modification in overweight/obese adolescents. Methods: A randomized, single-blind clinical trial with a control group, which aims to recruit 120 overweight/obese adolescents aged between 15-18 years (BMI ≥ 85th percentile). The sample will be selected through announcements in print media, social networks, television and radio. Groups will meet weekly over three months. The control group will receive a traditional health education intervention using pedagogy of transmission. The experimental group will receive a group-based motivational interdisciplinary intervention using a motivational interdisciplinary protocol based on the transtheoretical model of change. Conclusions: The results of this randomized clinical trial will determine if the motivational interdisciplinary intervention based on the transtheoretical model of change has an impact on lifestyle modification of the overweight/obese adolescents. If successful, the MERC program has the potential for application in different treatment scenarios, including that of the public health system. Trial Registration: The protocol for this study is registered with the Clinical Trial Registry (NTC02455973) and the Brazilian Registry of Clinical Trials (RBR-234nb5).